4TH INDUSTRIAL REVOLUTION AND CHALLENGES FOR EUROPEAN LAW (WITH SPECIAL ATTENTION TO THE CONCEPT OF DIGITAL SINGLE MARKET) (EU and comparative law issues and challenges series (ECLIC), 2018)
Digital Technologies alter our everyday life and the world around us. Individuals and businessmen are confronted with significantly differentiated conditions in every area of social-economic relations in contrast with the state that existed a few years ago. These altered conditions are in the case of the European Union’s Member States multiplied by this status and by the related facts, especially by the necessity to conform the domestic politics to the EU’s politics in many areas. Frontal offensive towards the creation of the digital single market was announced by the European Commission in May 2015 by releasing its 16 initiatives within three basic pillars. The year 2017 was characterized by various legislative activities motivated by the creation of optimal legislative conditions in the EU. Slovak Presidency of the Council of the EU was also significantly defined by the Digital Single Market Agenda, since the presidency’s program explicitly states the new key aim of the EU to ensure the free flow of data as the 5th freedom within the EU’s internal market. The Article analyses the most significant legislative changes introduced in 2017 which impact will be observable in the beginning of 2018 and in the following years.